2020
DOI: 10.1021/acsnano.0c03150
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymer Self-Assembly-Directed and Transient Laser Heating-Enabled Nanostructures toward Phononic and Photonic Quantum Materials

Abstract: Three-dimensional (3D) periodic ordering of silicon (Si), an inorganic semiconductor, on the mesoscale was achieved by combining block copolymer (BCP) self-assembly (SA) based mesoporous alternating gyroidal network formation with nonequilibrium transient laser heating. 3D continuous and periodically ordered alternating gyroidal mesoporous carbon thin-film networks were prepared from spin coating, SA under solvent vapor annealing (SVA), and thermal processing of mixtures of a triblock terpolymer with resorcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…The self-assembly of block copolymers has been extensively used to prepare a large variety of photonic and plasmonic structures, including lamellae, hexagonally-packed cylinders, [7,8] closely-packed micelles, [9,10] double diamond, [11] gyroids, [12,13] correlated networks and cubic, [14,15] and photonic glasses. [8,[16][17][18] Despite this wide variety, the most commonly reported architecture is by far based on the lamellar structure, as it is both simple to obtain and offers the best performance with respect to the optical response (i.e., maximal reflectivity from the smallest size).…”
Section: Block Copolymer Self-assembly For Photonic Structuresmentioning
confidence: 99%
“…The self-assembly of block copolymers has been extensively used to prepare a large variety of photonic and plasmonic structures, including lamellae, hexagonally-packed cylinders, [7,8] closely-packed micelles, [9,10] double diamond, [11] gyroids, [12,13] correlated networks and cubic, [14,15] and photonic glasses. [8,[16][17][18] Despite this wide variety, the most commonly reported architecture is by far based on the lamellar structure, as it is both simple to obtain and offers the best performance with respect to the optical response (i.e., maximal reflectivity from the smallest size).…”
Section: Block Copolymer Self-assembly For Photonic Structuresmentioning
confidence: 99%
“…2,5,7 Alternative nonequilibrium methods have been explored for the rapid formation of single crystal and polycrystalline inorganic nanostructures on shorter time frames. [20][21][22][23][24][25][26][27][28][29] For example, Tan et al demonstrated an all-laser-induced approach coupling BCP-directed self-assembly of resols with sub-millisecond laser heating (B-WRITE) to write hierarchically mesoporous polymer and carbon thin film structures. 21 Periodically ordered mesoporous crystalline silicon nanostructures were then obtained by filling the continuous network polymer template with amorphous silicon, followed by nanosecond laser-induced melt-crystallization and template removal.…”
Section: Main Textmentioning
confidence: 99%
“…21 Periodically ordered mesoporous crystalline silicon nanostructures were then obtained by filling the continuous network polymer template with amorphous silicon, followed by nanosecond laser-induced melt-crystallization and template removal. [21][22][23] Microwave annealing of mesoporous metal oxide thin films has been described but it required several minutes attaining limited crystallinity. 25 More recently, Hu et al and Tour et al reported a rapid Joule heating-based method generating discrete high-entropy metal nanoparticles, 26,27 sintered pellets of garnet ceramics with low porosity 28 and turbostratic graphene layers 29 on the milli-to tens of second timescales.…”
Section: Main Textmentioning
confidence: 99%
“…They have found use in wide-ranging applications in areas including photonics, separation, and purification, , and energy conversion and storage, , among others. In particular, due to their periodic self-organization on the mesoscale with lattice constants typically of order tens of nanometers, use of BCPs as self-assembling lithographic masks or templates in nanofabrication has been a highly researched area for several decades. , BCPs have been shown as capable of defining 2D and 3D periodic structures in relevant organic and inorganic materials through the process of structure direction using solution-based approaches like solvent evaporation induced self-assembly. , Numerous materials classes including transition metal oxides and nitrides, nonoxide ceramics, metals, and semiconductors have been architecturally defined on the nanoscale by BCP self-assembly in this way through methods amenable to traditional semiconductor manufacturing. …”
Section: Introductionmentioning
confidence: 99%